2020
DOI: 10.1155/2020/5721258
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research on Methods to Improve Tumor Hypoxia Environment

Abstract: Cancer is a major disease burden worldwide. In recent years, in addition to surgical resection, radiotherapy and chemotherapy are recognized as the most effective methods for treating solid tumors. These methods have been introduced to treat tumors of different origins and stages clinically. However, due to insufficient blood flow and oxygen (O2) supply in solid tumors, hypoxia is caused, leading to decreased sensitivity of tumor cells and poor therapeutic effects. In addition, hypoxia will also lead to resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 149 publications
0
10
0
Order By: Relevance
“…It is one of the important strategies to improve tumor oxygen content through constructing a direct O 2 delivery nanoplatform and then delivering O 2 into the hypoxic TME. [ 25 ] For RT and chemotherapy, relieving tumor hypoxia can improve the sensitivity of tumor cells to radiation and chemotherapeutic drugs and enhance the therapeutic effect. For some catalytic treatments involving oxygen, carrying oxygen can provide more raw materials to enhance catalytic treatment.…”
Section: Direct Oxygen Delivery Nanoplatformmentioning
confidence: 99%
“…It is one of the important strategies to improve tumor oxygen content through constructing a direct O 2 delivery nanoplatform and then delivering O 2 into the hypoxic TME. [ 25 ] For RT and chemotherapy, relieving tumor hypoxia can improve the sensitivity of tumor cells to radiation and chemotherapeutic drugs and enhance the therapeutic effect. For some catalytic treatments involving oxygen, carrying oxygen can provide more raw materials to enhance catalytic treatment.…”
Section: Direct Oxygen Delivery Nanoplatformmentioning
confidence: 99%
“…[ 27 ] Hypoxia also exacerbates the abnormal metabolism of cancer cells resulting in an acidic environment of tumor tissue, leading to a significant increase in H 2 O 2 inside the tumor. [ 28 ] Although PDT combined with cancer treatments has some benefits, it is affected by the tumor microenvironment (TME). [ 29 ] Oxygen is the key substrate of PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Since PDT is an oxygen-dependent process, the hypoxic environment at the tumor site is an obstacle to ROS generation and limits the therapeutic effect of PDT. , Therefore, possibilities for in situ oxygen-production at the tumor site have been investigated . Nanocrystalline MnO 2 undergoes Fenton-like reaction in the acidic microenvironment of tumors (eqs and ), oxidizing endogenous hydrogen peroxide and producing oxygen and toxic hydroxide radicals, which is indeed also recognized as chemodynamic therapy (CDT). , Ni et al have shown the decomposition of H 2 O 2 to generate O 2 using CuS NPs wrapped on the surface of upconversion NPs via MnO 2 coating.…”
Section: Introductionmentioning
confidence: 99%